Possibilidades da liberdade conforme a filosofia crítica de Kant - Araújo, Mariana Frutuoso (2017)
The idea of freedom is defined by Kant in the critique of pure reason as a transcendental idea of reason, the philosopher investigates the metaphysical problem of freedom and the determinism that is discussed within the conflict of cosmological antinomic propositions. That problem characterizes the investigation if in the world all causality must be attributed to natural laws or whether there is also causality for freedom. The transcendental idea of freedom is defined as a spontaneity able to initiate a series of events that takes place in nature. In the Groundwork of the Metaphysic of Morals, Kant lays the foundation for the supreme principle of morality Based on the transcendental idea of freedom, that serves as a model to think about freedom in a practical sense, that is, as regards human actions. The Concept of transcendental freedom is the key to explaining the autonomy of the will of human beings, because the concept of freedom necessary assumption for the idea of unconditional imperative Is understood as the concept of morality. However as the concept of freedom is not constitutive, but only imagined, The practical philosophy requires that there is no way to attribute freedom to a rational being without demonstrating as a fact the objective reality of this concept. As a consequence, in Critique of Practical Reason Kant Reversed the order of concepts and put as necessary investigate the validity of the categorical imperative from the moral conscience understood as the fact of reason, Kant believes that with proof of morality as fact of reason, is equivalent to the objective proof of freedom. In view of these considerations, this work proposes to gather the arguments presented in Critique of Pure Reason, in Groundwork of the Metaphysic of Morals and the Critique Practical Reason, that argue the relationship between freedom and human reason, in order to investigate the possibility of freedom for man. We first describe the way in which reason thinks the idea of freedom From the discussion of the third antinomy, and the solution presented by Kant for this conflict of reason, making a transition from the discussion in a theoretical sense to the practical meaning on which the possibility of pure practical philosophy depends. Therefore, we investigated the Kantian foundation of morality to understand the autonomy of the human will based on the concept of freedom. It became necessary, because, the proof of the objective reality of freedom, thus, we try to prove whether the proof of the reality of morality from the fact of reason, offers equally a proof of freedom. Faced with the impossibility of an empirical objectification of freedom the definition of the practical scope as the field that practical reason can be realized, Composes the place of freedom in the architectural of the pure reason of the Kantian critical system